Identification of the Extradural and Intradural Extension of Pituitary Adenomas to the Suprasellar Region: Classification, Surgical Strategies, and Outcomes - Yang, YouQing; Bao, YouYuan; Xie, ShenHao; Tang, Bin; Wu, Xiao; Yang, Le; Wu, Jie; Ding, Han; Li, ShaoYang; Zheng, SuYue; Hong, Tao (Frontiers in Oncology, 2021)
Objective Suprasellar pituitary adenomas (PAs) can be located in either extradural or intradural spaces, which impacts surgical strategies and outcomes. This study determined how to distinguish these two different types of PAs and analyzed their corresponding surgical strategies and outcomes. Methods We retrospectively analyzed 389 patients who underwent surgery for PAs with suprasellar extension between 2016 to 2020 at our center. PAs were classified into two main grades according to tumor topography and their relationships to the diaphragm sellae (DS) and DS-attached residual pituitary gland (PG). Grade 1 tumors were located extradurally and further divided into grades 1a and 1b, while grade 2 tumors were located intradurally. Results Of 389 PAs, 292 (75.1%) were surrounded by a bilayer structure formed by the DS and the residual PG and classified as grade 1a, 63 (16.2%) had lobulated or daughter tumors resulting from the thinning or absence of the residual PG and subsequently rendering the bilayer weaker were classified as Grade 1b, and the remaining 34 (8.7%) PAs that broke through the DS or traversed the diaphragmic opening and encased suprasellar neurovascular structures were classified as Grade 2. We found that the gross total removal of the suprasellar part of grade 1a, 1b, and 2 PAs decreased with grading (88.4%, 71.4%, and 61.8%, respectively). The rate of major operative complications, including cerebrospinal fluid leakage, hemorrhage, and death, increased with grading. Conclusions It is essential to identify whether PAs with suprasellar extension are located extradurally or intradurally, which depends on whether the bilayer structure is intact. PAs with an intact bilayer structure were classified as grade 1. These were extradural and usually had good surgical outcomes and lower complications. PAs with no bilayer structure surrounding them were classified as grade 2. These were intradural, connected to the cranial cavity, and had increased surgical complications and a lower rate of gross total removal. Different surgical strategies should be adopted for extradural and intradural PAs.